The trouble with Africa why foreign aid isn't working - Calderisi, Robert (Palgrave Macmillan Palgrave Macmillan, 2006)
After years of frustration at the stifling atmosphere of political correctness surrounding discussions of Africa, long time World Bank official Robert Calderisi speaks out. He boldly reveals how most of Africa's misfortunes are self-imposed, and why the world must now deal differently with the continent.
Includes bibliographical references (p. [239]-241) and index.
Keywords: Economic assistance--Africa.